Heritage Impact Assessment Index Within Urban Development Context: The Case of Masjed-e Jame of Isfahan in Iran - Baharak Ashrafi; Michael Kloos; Christa Reicher (Heritage)
Despite various opportunities, urban development projects have been causing significant challenges to the preservation and conservation of historic cultural heritage. In particular, an increasing number of World Heritage (WH) properties are impacted by the direct and indirect effects of development projects, reflecting the existing uprising conflict. Grasping the challenge, Heritage Impact Assessment (HIA) has been developed as a proactive assessment tool to identify and predict potential impacts, mitigate the negative impacts on heritage values, and sustain the attributes conveying OUVs in WH assets. The growing demand for urban development and its potential impacts on cultural heritage properties underscores the necessity for the development of a targeted Heritage Impact Assessment methodology for urban development threats. To adequately address multiple impacts, this paper proposes a triangulation of a qualitative matrix for impact identification and a semi-quantitative indicator-based index for impact analysis and evaluation. The methodology is applied to the World Heritage property of Masjed-e Jame of Isfahan in Iran. In drawing upon this example, a systematic and integrated impact assessment procedure is developed to capture a broad category of potential impacts and their significance that is crucial for determining site-specific mitigation strategies and informed decision-making within the context of heritage management and sustainable urban development.